Expression of ESAT‐6 antigen from Mycobacterium tuberculosis in broccoli: An edible plant. (2nd January 2020) - Saba, Kiran; Sameeullah, Muhammad; Asghar, Asba; Gottschamel, Johanna; Latif, Sara; Lössl, Andreas Günter; Mirza, Bushra; Mirza, Osman; Waheed, Mohammad Tahir
Abstract: Tuberculosis (TB) is one of the major infectious diseases caused by Mycobacterium tuberculosis . The development of an effective and economical vaccine for controlling TB is essential especially for developing countries. Edible plants can serve as biofactories to produce vaccine antigens. In this study, 6 kDa early secretory antigenic target (ESAT‐6) of M. tuberculosis was expressed in Brassica oleracea var. italica via Agrobacterium ‐mediated transformation to facilitate oral delivery of antigen. ESAT‐6 gene was cloned using Gateway® cloning strategy. Transformation and presence of transgene was confirmed through PCR. Expression level of transgene was calculated via quantitative real‐time PCR (qRT‐PCR) and the maximum integrated transgene number was two. Maximum amount of total soluble fraction of ESAT‐6 was evaluated by immunoblotting, estimated to accumulate up to 0.5% of total soluble protein. The recombinant ESAT‐6 protein was further purified and detected using silver staining and Western blotting. ESAT‐6 protein induced humoral immune response in mice immunized orally and subcutaneously. The expression of M. tuberculosis antigen in edible plants could aid in the development of cost‐effective and oral delivery of an antigen‐based subunit vaccine against TB. To the best our knowledge, it is the first report of expression of a vaccine antigen in broccoli. Abstract :